GEOMORPHIC EVOLUTION OF WESTERN (PALIKI) KEPHALONIA ISLAND (GREECE) DURING THE QUATERNARY - Gaki - Papanastassiou, K.; Karymbalis, E.; Maroukian, H.; Tsanakas, K. (Bulletin of the Geological Society of Greece, 2010)
Kephalonia Island is located in the Ionian Sea (western Greece). The active subduction zone of the African lithosphere submerging beneath the Eurasian plate is placed just west of the island. The evolution of the island is depended mostly on the geodynamic processes derived from this vigorous margin. The geomorphic evolution of the western part of the island (Paliki peninsula) during the Quaternary was studied, by carrying out detailed field geomorphological mapping focusing on both coastal and fluvial landforms, utilizing aerial photos and satellite image interpretation with the use of GIS technology. The coastal morphology of Paliki includes beachrocks, aeolianites, notches and small fan deltas which were all studied and mapped in detail. The drainage systems of the peninsula comprise an older one on carbonate formations in the northwest and a younger Quaternary one in the south and southeast. Eight marine terraces found primarily on the Pliocene marine formations range in elevation from 2 m to 440 m are tilted to the south. In the Late Pleistocene some of the main drainage networks flowed towards the newly-formed gulf of Argostoli to the east.